PROCESSING OF COCONUT SHELL AND FIBER FOR ADDING VALUE - CORTEZ, LUIS A. B.; PEREZ, JUAN M. M.; ROCHA, JOSÉ D.; JORDAN, RODRIGO A.; MESA, HENRY R. M. (Revista Brasileira de Engenharia de Biossistemas, 2009)
Currently Brazil is the largest producer of green coconut, with a planted area equivalent to 57 thousandhectares, where most of the production (66.5%) is concentrated in the Northeast region. Afterconsumption of the coconut water, the residue is a problem for waste disposal systems. Due to itsslow natural degradation, the coconut fiber lasts a long time. This research shows the results of slowpyrolysis of the fiber and the green coconut shell. The experiments were conducted in a smallexperimental furnace at a temperature of 350°C. The results showed that the fixed carbon yield as74.43% for green cored and 58.07% for green mesocarp. The ash contents of the same sampleswere 14.13% and 13.03% respectively. The levels of volatiles were 11.40% for charcoal producedfrom the green core, and 28.90% for charcoal from the green mesocarp. The experimentsdemonstrated that the green coconut residue has potential for charcoal production. The results foundin this research can change in industrial production scale, a pilot plant is highly recommended toprove the raw material and technology performances. The overall yields must also be studied carefullyfor larger scale systems. Aspects such as costs, logistics, and raw material pre-treatment need alsobe assessed in case that a future production plant is decided to be built